1995
DOI: 10.1039/c39950001859
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective reduction of 4-tert-butylcyclohexanone to cis-4-tert-butylcyclohexanol catalysed by zeolite BEA

Abstract: Zeolite BEA is found to be the first stereoselective and regenerable heterogeneous catalyst for the Meerwein-Ponndorf-Verley reduction of 4-tert-butylcyclohexanone to cis-4-tert-butylcyclohexanol.The Meenvein-Ponndorf-Verley (MPV) reduction of aldehydes and ketones is a highly selective reaction that can be performed under mild conditions, without affecting other reducible functional groups. The hydrogen donors are easily oxidizable secondary alcohols and the reductions are usually catalysed by metal alkoxides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 6 publications
1
29
0
Order By: Relevance
“…This is consistent with the literature data for the MPV reactions in the liquid phase [7,25] as well as the gas-phase results that were obtained using a higher partial pressure of IPA [24]. Higher cis-than tr-4-TBCHL selectivity in the zeolite Beta-catalyzed MPV reactions is hypothesized to be due to the fact that the cis-transition state can be easily accommodated within the straight channels of zeolite Beta, whereas the bulkier tr-transition state cannot [26]. As illustrated in Fig.…”
Section: Catalytic Selectivitysupporting
confidence: 89%
“…This is consistent with the literature data for the MPV reactions in the liquid phase [7,25] as well as the gas-phase results that were obtained using a higher partial pressure of IPA [24]. Higher cis-than tr-4-TBCHL selectivity in the zeolite Beta-catalyzed MPV reactions is hypothesized to be due to the fact that the cis-transition state can be easily accommodated within the straight channels of zeolite Beta, whereas the bulkier tr-transition state cannot [26]. As illustrated in Fig.…”
Section: Catalytic Selectivitysupporting
confidence: 89%
“…43,44 Several methods of activation of aluminum isopropoxide, e.g., by microwave irradiation, 45 by zeolite, 46 and by grafting on MCM-41, 47 have been recently studied. Inorganic Mg-Al hydrotalcite was also used as a catalyst of the MPV reduction.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Al-and Ti-zeolites have been reported as excellent catalysts for MPVO reactions, and it was shown that Lewis acid sites were the active sites of the catalyst. Thus, Creyghton et al [188,189] reported the stereoselective reduction of 4-tert-butylcyclohexanone to cis-4-tert-butylcyclohexanol (>95%) (which is a fragrance chemical intermediate) in liquid phase using Beta zeolite as catalyst (Scheme 25.36).…”
Section: Meerwein-ponndorf Verley Reduction and Oppenauer Oxidation (mentioning
confidence: 99%